Immune Reactions in the Body Based on Listeriosis. - Hamidova Saodat Khikmatovna (Genius Journals, 2022)
The review presents data on the antigenic structure of Listeria and the modern classification of epidemically significant Listeria serovariants. Information is given on the characteristic species-specific properties of Listeria serovariants, which may be common to two or more species, and also have common antigens with staphylococci, typhoid-paratyphoid bacteria.
Keywords: listeria; paratyphoid bacterium; antigenic scheme; listeriosis